Samurai and Supermen : national socialist views of Japan - Maltarich, Bill (German life and civilization, 2005)
Focusing on the ideological contradictions inherent in the German alliance with Japan during World War II, this book analyses German discourse about Japan from the distinct yet intricately connected standpoints of the German-Japanese historical relationship, the scientific and pseudo-scientific presentation of Japan in Germany, and German fictional depictions of Japan. The volume examines the historical relationship between Germany and Japan in the light of their alliance. It also traces the origins and development of the image of Japan in Nazi Germany. Through non-fiction texts, the points of emphasis, friction, and outright contradiction are discovered between Nazi ideology and an alliance with Japan as they were discussed both publicly and privately in Germany at the time. Finally, by examining fictional depictions of Japan and the Japanese under the Nazis, the work reveals the means by which fiction addressed these ideological issues and incorporated the historical and non-fictional arguments of its contemporaries. This book looks carefully at its connection to other historical, political, racial, and ideological thought of the time.